Teacher Education as a Profession : In Search of Quality Teacher - Suharno, Suharno (ETERNAL, 2010)
Abstract For the last 50 years educators have spent a great deal of energy and time to the debate over whether teaching can be classified as a profession.Â This paper aims to elaborate the issues of teacher education as a profession and the attempts of classifying characteristics of quality teachers. Teacher education itself is intended to improve the teacherâs skills and knowledge and there have been some approaches for the teacher development such as teacher-as-researcher, action research, clinical supervision, reflective teaching, etc. From the teacher education or development we can figure out some features of effective or quality teachers. Â Key words: teacher education, profession, quality teacher, approach, research